Long-term Orientation of Family Firms An Investigation of R&D Investments, Downsizing Practices, and Executive Pay - Block, Jörn (Innovation und Entrepreneurship, 2009)
Recently, firms have been criticized for focusing too strongly on the short term and for neglecting investments in assets and capabilities required for long-term success, such as investments in R&D or in employee training. Family firms are considered to be different. They are commonly assumed to be more long-term oriented than comparable non-family firms. Joern Block analyzes this phenomenon in more detail and investigates whether and under which conditions family firms pursue more long-term oriented strategies than other firms. To this end, he compares R&D activities, downsizing practices and executive compensation of family firms with those of non-family firms. He also develops a theoretical model of how to pay a non-family manager who works in a family firm.